2012
DOI: 10.1111/jen.12027
|View full text |Cite
|
Sign up to set email alerts
|

Green peach aphid [Myzus persicae (Sulzer) (Hemiptera: Aphididae)] control using Brassicaceae ethyl ester oil sprays

Abstract: Control of green peach aphid (Myzus persicae), a globally important pest, using plant‐derived oils is a promising alternative to conventional insecticides. Although various plant‐derived oils are potentially useful for insect control, dose–response studies and efficacy comparisons among oils have not been widely reported. Our objective was to compare M. persicae control by plant‐derived oils, focusing on oils derived from Brassicaceae species that exhibit rotational and environmental quality benefits. We thus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 32 publications
2
8
0
Order By: Relevance
“…A pronounced differences were estimated in the case of treatment with green algae extract in one site and red algae extract or control in another site. Similar results were obtained by Hansson et al (2012), they proved the presence of ethyl ester in tomato extract. Tikunov et al (2005), also, recognized hexadecanoic acid, ethyl ester in tomato plant extract (Lycopersicone sculentum) genotype.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…A pronounced differences were estimated in the case of treatment with green algae extract in one site and red algae extract or control in another site. Similar results were obtained by Hansson et al (2012), they proved the presence of ethyl ester in tomato extract. Tikunov et al (2005), also, recognized hexadecanoic acid, ethyl ester in tomato plant extract (Lycopersicone sculentum) genotype.…”
Section: Resultssupporting
confidence: 88%
“…Similar results were obtained by Juliana et al (2016) they recognized phytol as bioactive compound of tomato extract. Also, Hansson et al (2012) reported that treatment with green algae (Ulva lactuca) extract led to an increase in the concentration of some biologically important compounds such as Tetraacetyl-d-xylonic nitriled -as in Figure 5. This compound have bioefficiency as stated in the study at Imad et al (2015).…”
Section: Fig 4 Phytolmentioning
confidence: 96%
“…Table (1) demonstrated that, although the extract concentrations were low, the mortality rate of the adults of Aphis gossypii was high and when the concentrations increased, the total mortality increased. These results were in agreement with Hansson et al (2012) which proved the effectiveness of ethyl ester oil on Myzus persicae. Table (3) and Fig.…”
Section: Methods Of Application:-spray Method:-supporting
confidence: 81%
“…Thus, this study was undertaken to determine the potential plant extract activities and to provide data for future studies. It was reported that there may be increases in insecticidal and enzyme inhibition periods in parallel with the increase in plant extract concentrations (Junqing et al, 2011;Hansson et al, 2012). In the literature, it is mentioned that plant metabolite alkaloids and terpenes can have significant insecticide effects; however, they are not economic or safe in addition to the fact that they are difficult to isolate (Rattan, 2010).…”
Section: Resultsmentioning
confidence: 99%